OPTICAL METHODS FOR MONITORING OF VOLCANOES: TECHNIQUES AND NEW PERSPECTIVES - De Natale P.; Gianfrani L.; De Natale G. (My University, 2001)
Present optical techniques, which are considered to be relevant to monitor volcanoes, are reviewed. A short description of each technique is given, as well as the peculiar conditions of applicability. Recent experimental results taken at Solfatara crater with a fiber-coupled diode laser system are reported and discussed. To take into account the tremendous progress that is experiencing the field of new laser sources and optical materials, an overview to future laser devices, that may have a significant impact in the field of gas monitoring, is given.